Implementasi Kebijakan Keamanan Dan Keselamatan Wisatawan: Studi Kasus Umbul Ponggok Klaten - Ade Yuliar; Riko Setyawan; Rini Wulandari (Jurnal Penelitian Ilmu Pariwisata, 2025)
The tourism sector must have security and safety standards set by the Indonesian Minister of Tourism and Creative Economy. This study aims to determine how the implementation of Standard Operating Procedures (SOP) at the Umbul Ponggok tourist attraction. This research is a field research, namely research whose data is obtained directly from the location studied. The method used in writing this research is descriptive qualitative, data acquisition using observation, interviews, and documentation. The results of the study indicate that the implementation of security and safety SOPs has been met according to the guidelines at the Umbul Ponggok tourist attraction in terms of three factors, namely from the Human Resources (HR) factor including HR including competent operational staff in the water tourism business, accompanied by training programs, performance evaluations, career development; then the safety and comfort facility factor includes first aid and oxygen according to standards, activity equipment, communication tools, life jackets, and the availability of prayer areas, and the minimum facility factor for water businesses includes infrastructure including administration and office rooms, guest and employee areas, medical rooms, communication equipment, repair rooms, dining areas, fire extinguishers, shower rooms, toilets, electricity and clean water installations, and emergency access for tourists. Standardization exists for the implementation of SOPs, but consistency remains lacking. Supporting and inhibiting factors exist in implementing SOPs related to tourist safety and security, which refer to tourism laws and ministerial regulations.